Nature, Risk and Responsibility
X, 232 p.
Keywords: Nature, Risk and Responsibility explores ethical interpretations of biotechnology and examines whether sufficient consensus exists or is emerging to enable this technology to occupy a stable role in the techno-economic, social and cultural order. The contributors address the nature and prospective implications of biotechnologies for nature, life and social organisation and employ a wide range of social theories to evaluate risks and propose responses.